Functional analysis of the bZIP-type transcription factors AtfA and AtfB in Aspergillus nidulans - Kocsis, Beatrix; Lee, Mi-Kyung; Yu, Jae-Hyuk; Nagy, Tibor; Daróczi, Lajos; Batta, Gyula; Pócsi, István; Leiter, Éva (Frontiers in Microbiology, 2022)
Transcription factors (TFs) with the basic leucin zipper domain are key elements of the stress response pathways in filamentous fungi. In this study, we functionally characterized the two bZIP type TFs AtfA and AtfB by deletion (Δ) and overexpression (OE) of their encoding genes in all combination: ΔatfA, ΔatfB, ΔatfAΔatfB, ΔatfAatfBOE, ΔatfBatfAOE, atfAOE, atfBOE and atfAOEatfBOE in Aspergillus nidulans. Based on our previous studies, ΔatfA increased the sensitivity of the fungus to oxidative stress mediated by menadione sodium bisulfite (MSB) and tert-butylhydroperoxide (tBOOH), while ΔatfB was not sensitive to any oxidative stress generating agents, namely MSB, tBOOH and diamide at all. Contrarily, the ΔatfB mutant was sensitive to NaCl, but tolerant to sorbitol. Overexpression of atfB was able to compensate the MSB sensitivity of the ΔatfA mutant. Heavy metal stress elicited by CdCl2 reduced diameter of the atfBOE and atfAOEatfBOE mutant colonies to about 50% of control colony, while the cell wall stress generating agent CongoRed increased the tolerance of the ΔatfA mutant. When we tested the heat stress sensitivity of the asexual spores (conidiospores) of the mutants, we found that conidiospores of ΔatfAatfBOE and ΔatfBatfAOE showed nearly 100% tolerance to heat stress. Asexual development was negatively affected by ΔatfA, while atfAOE and atfAOE coupled with ΔatfB increased the number of conidiospores of the fungus approximately 150% compared to the control. Overexpression of atfB led to a 25% reduction in the number of conidiospores, but increased levels of abaA mRNA and size of conidiospores. Sexual fruiting body (cleistothecium) formation was diminished in the ΔatfA and the ΔatfAΔatfB mutants, while relatively elevated in the ΔatfB and the ΔatfBatfAOE mutants. Production of the mycotoxin sterigmatocystin (ST) was decreased to undetectable levels in the ΔatfA mutant, yet ST production was restored in the ΔatfAΔatfB mutant, suggesting that ΔatfB can suppress ST production defect caused by ΔatfA. Levels of ST were also significantly decreased in the ΔatfAatfBOE, ΔatfBatfAOE and atfAOEatfBOE mutants.